Recent Increase in Meningitis Caused by Neisseria meningitidis Serogroups A and W135, Yaoundé, Cameroon - Marie-Christine Fonkoua; Muhamed-Kheir Taha; Pierre Nicolas; Patrick Cunin; Jean-Michel Alonso; Raymond Bercion; Jeanne Musi; Paul M.V. Martin (Emerging Infectious Diseases, 2002)
From 1991 to 1998, Neisseria meningitidis serogroups A, B, and C represented 2%-10% of strains isolated from cases of bacterial meningitis in Yaoundé. During 1999 to 2000, the percentage of meningococci reached 17%, a proportion never reported since recordkeeping began in 1984. The increase of serogroup A meningococci and the emergence of W135 strains highlight the need for increased surveillance for better diagnosis and prevention.